Nano-Safety : What We Need to Know to Protect Workers - Aquino, Grace V.; Asmatulu, Eylem; Asmatulu, Ramazan; Fazarro, Dominick; Foster, Barbara; Hanks, Craig; Hernandez, Roger A.; Hirt, Evelyn H.; Kay Hanks, Emily; Khan, W. S.; Newberry, Deb; Sayes, Christie; et al. (De Gruyter, 2017)
Nanotechnology safety is the practice of handling engineered nanomaterials in production and manufacturing. Good practice consists of understanding and interpreting Material Safety Data Sheets, behaving safely when working with yet unknown nanomaterials, understanding health effects, and proactively creating safety measures against potential hazards. This book introduces nanotechnology risk management to readers from academia and industry.
Keywords: Nanotechnology -- Safety measures.; Nanotechnology -- Safety regulations.; Nanotechnologie -- Sécurité -- Mesures.; Nanotechnologie -- Sécurité -- Règlements.; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference.; Nanotechnology; Electronic books.; Safety regulations